Diseño de una Infraestructura Hospitalaria de Segundo Nivel para la Ciudad de Atuntaqui - Mina García, Edison Xavier (2023)
The present final degree project called 'Second level hospital infrastructure for the city of Atuntaqui', seeks to respond to the needs of the Antonio Ante canton, and increase the capacity of the public health system of the province of Imbabura. a study and subsequent architectural design of a General Teaching Hospital, which will be located in the cantonal head, in order to complement the service of the San Vicente de Paul Hospital in the city of Ibarra. This work will show a different perspective in the conception of hospital architecture, using scientific concepts from neurosciences applied to the conception of comfortable and efficient spaces that help and influence the good recovery of patients and the development of hospital personnel. Health. The project proposes to design therapeutic environments achieved through the application of Neuroarchitecture concepts, in order to determine the perception of space and how it directly influences the recovery of patients. In a first stage, the problem addressed from its antecedents will be contextualized and the different aspects covered by neurosciences will be analyzed. With the specific definition of the research question to be treated, the development of the methodology is presented, in which it begins with a conceptual structure of a humanized hospital architecture. Subsequently, the context will allow us to identify the historical development of hospital facilities in the country, through current regulations and the minimum needs that each health service provider entity must meet for its operation. With this theoretical approach and in order to improve the conditions of the health service in the province of Imbabura, the aim is to create an efficient hospital establishment based on interior and exterior spaces, which contribute to generating curative environments, according to the Neuroarchitecture.